Drug release, preclinical and clinical pharmacokinetics relationships of alginate pellets prepared by melt technology. (2nd January 2016) - Bose, Anirbandeep; Harjoh, Nurulaini; Pal, Tapan Kumar; Dan, Shubhasis; Wong, Tin Wui
Abstract : Introduction: Alginate pellets prepared by the aqueous agglomeration technique experience fast drug dissolution due to the porous pre-formed calcium alginate microstructure. Objective: This study investigated in vitro drug release, preclinical and clinical pharmacokinetics relationships of intestinal-specific calcium acetate-alginate pellets against calcium-free and calcium carbonate-alginate pellets. Method: Alginate pellets were prepared by solvent-free melt pelletization instead of aqueous agglomeration technique using chlorpheniramine maleate as model drug. Results: A fast in situ calcium acetate dissolution in pellets resulted in rapid pellet breakup, soluble Ca 2+ crosslinking of alginate fragments and drug dissolution retardation at pH 1.2, which were not found in other pellet types. The preclinical drug absorption rate was lower with calcium acetate loaded than calcium-free alginate pellets. In human subjects, however, the extent and the rate of drug absorption were higher from calcium acetate-loaded pellets than calcium-free alginate pellets. The fine, dispersible and weakly gastric mucoadhesive calcium alginate pellets underwent fast human gastrointestinal transit. They released the drug at a greater rate than calcium-free pellets in the intestine, thereby promoting drug bioavailability. Conclusion: Calcium acetate was required as a disintegrant more than as a crosslinking agent clinically to promote pellet fragmentation, fast gastrointestinal transit and drug release in intestinal medium, and intestinal-specific drug bioavailability.